INTEGRATION OF ISLAM AND LOCAL CULTURE TO BUILD CHARACTER EDUCATION IN EARLY CHILDHOOD - Suriadi, Suriadi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Local knowledge can be defined as a policy or noble values contained in the richness of the local culture in the form of traditions, manners and life motto. Speaking of local wisdom means talking about culture and culture as a result of human creativity. Academic studies in exploring the benefits of local integrating throughout early childhood education into the educational model of character with the expectation that students do not lose our identity and value cultural and insight knowledge of social reality and environment culturally amid onslaught of globalization and modernization that is sweeping cultural in Indonesia.